2003
DOI: 10.1086/376531
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Human T Cell Leukemia Virus Type I to Nucleoside Reverse Transcriptase Inhibitors

Abstract: A single-cycle infection assay with recombinant viral vectors was developed to study human T cell leukemia virus type I (HTLV-I) replication and its inhibition by antiviral agents. The susceptibility of HTLV-I to 6 nucleoside reverse-transcriptase inhibitors was examined. HTLV-I replication was inhibited by tenofovir, abacavir, lamivudine, zalcitabine, stavudine, and zidovudine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 18 publications
1
35
1
Order By: Relevance
“…However, another study reported that lamivudine had no definite effect on proviral load (34). In this study, administering tenofovir to block the spread of infection to new cells did not influence the proviral load in hu-PBMC-NOG mice, even though tenofovir has been reported to be more efficient in inhibiting HTLV-1 replication than lamivudine (20). Taken together, these results suggest that clonal proliferation contributes to the increase of HTLV-1-infected cells more than internal contagion even early in HTLV-1 infection.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…However, another study reported that lamivudine had no definite effect on proviral load (34). In this study, administering tenofovir to block the spread of infection to new cells did not influence the proviral load in hu-PBMC-NOG mice, even though tenofovir has been reported to be more efficient in inhibiting HTLV-1 replication than lamivudine (20). Taken together, these results suggest that clonal proliferation contributes to the increase of HTLV-1-infected cells more than internal contagion even early in HTLV-1 infection.…”
Section: Discussioncontrasting
confidence: 51%
“…A previous in vitro study reported that AZT was able to inhibit new HTLV-1 infection of human lymphocytes (37). In addition, it has been reported that tenofovir efficiently inhibited the reverse transcriptase activity of HTLV-1 (20). In order to assess whether a preventive antiretroviral treatment would prove useful in cases of accidental HTLV-1 exposure, we treated hu-PBMC-NOG mice with two reverse transcriptase inhibitors, AZT and tenofovir.…”
Section: Significant Increase In the Memory Cd4 ؉ T-cell Population Amentioning
confidence: 99%
“…Some of the cocultivation experiments were performed in the presence of Zerit (Bristol-Myers Squibb Virology, Princeton, NJ) (24). We treated long terminal repeat (LTR)-driven luciferase-expressing Raji cells with or without 35 M of Zerit the day before cocultivation with Jurkat T cells.…”
Section: Methodsmentioning
confidence: 99%
“…70 For example, in patients with HTLV-1-associated myelopathy (HAM), reduction of HTLV-1 viral DNA load was reported during treatment with the reverse transcriptase inhibitor lamivudine, 71 and HTLV-1 replication was inhibited by the nucleoside reverse-transcriptase inhibitors tenofovir, abacavir, lamivudine, zalcitabine, stavudine, zidovudine and didanosine. 72,73 Another report described the successful treatment of a patient with ATL using zidovudine, lamivudine and IFN-a. 74 Thus, antiretroviral treatment appears to be a promising strategy for the treatment of ATL as a viral infectious disease, but further studies are required in order to elucidate the mechanisms of the anti-ATL effects.…”
Section: New Chemical Anti-tumor Agents 1) Antiretroviral Therapymentioning
confidence: 99%